Vascularized Ulnar Transposition and Radioulnoscapholunate Fusion With Volar Locking Plate in a Dorsal Position Following Resection of Giant Cell Tumor of the Distal Radius. Issue 3 (September 2020) - Van Handel, Amelia C.; Galvez, Michael G.; Brogan, David M.; Boyer, Martin I.; Cipriano, Cara A.; Hirbe, Angela C.; Pet, Mitchell A.
Abstract : Giant cell tumor of the distal radius is a rare, locally destructive, and frequently recurrent tumor. We present a case of Campanacci Grade III giant cell tumor of the distal radius with pathologic fracture and cortical destruction which was treated with neoadjuvant denosumab. This facilitated en-bloc resection of the entire distal radius, including the articular surface, while minimizing tumor contamination. Reconstruction was accomplished using a vascularized ulnar transposition flap to facilitate radioulnoscapholunate fusion, which was fixated using a long-stem contralateral variable angle locking volar distal radius plate in a dorsal position. This case illustrates multidisciplinary management of a challenging reconstructive problem and demonstrates a novel strategy for fixation which repurposes familiar and readily available hardware to provide optimal osteosynthesis.